Antimicrobial prophylaxis in hematopoietic stem cell transplantation recipients: 10 years after. Issue 4 (22nd May 2014) - Trifilio, S.; Mehta, J.
Abstract Background Antimicrobial prophylaxis is recommended for all patients undergoing hematopoietic stem cell transplantation. Evidence‐based guidelines recently have been updated to incorporate the results from recent clinical studies. Methods An antimicrobial prophylaxis survey was conducted during the 2013 ASBMT Tandem Meetings to discern the degree of concordance between transplant centers and society guidelines. Results The results show significant differences in prescribing practices among transplant institutions and variance with evidence‐based guidelines. Conclusion The clinical significance of this discordance is unknown.